Pengembangan Kapasitas SDM dan Edukasi Kewirausahaan dalam Meningkatkan Potensi UMKM Desa Sukamukti: Human Resource Capacity Development and Entrepreneurship Education in Increasing the Potential of MSMEs Desa Sukamukti - Hilmiana Hilmiana; Adhitya Nisrina Putri; Arthamevia Najwa Soraya; Britania Angela Ibrani; Rahmatania Rahmatania; Salsabila Iftikhar Imana; Syahra Aliva Winma; Dara Sagita Triski (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Sukamukti Village has significant potential in the MSME sector, which plays a crucial role in creating jobs and improving community welfare. However, MSME development in this village still faces various obstacles, particularly related to the quality of human resources and the limited number of jobs available to the community. Based on initial observations and interviews with business owners, it was found that most MSME owners still face limitations in business management, particularly in digital marketing and job development. This condition indicates that a community needs to improve its entrepreneurial capacity and job skills more relevant to local economic development. This activity aims to improve human resource capacity and develop the potential of MSMEs in Sukamukti Village through entrepreneurship education and job skills training. The method used was a qualitative approach, including field observations and structured interviews with five local MSME owners across culinary businesses, material stores, laundry businesses, wedding organizers, and pharmacies. The results of the activity showed that most business owners face challenges in business management, particularly in managerial and digital marketing areas. Through entrepreneurship education and pre-employment training, the community gained an understanding of business management, job opportunities, and the use of digital technology to support business activities. The conclusions of this activity indicate that increasing human resource capacity through education and training can be a strategy for strengthening MSME development and expanding community employment opportunities. This activity was evaluated through participant feedback and observations, indicating increased community knowledge and readiness to develop independent businesses.